Determinan Faktor Yang Memengaruhi Minat Wajib Pajak Dalam Penggunaan E-Filing (Studi Empiris Pada KPP Pratama Jayapura) - Muslimin, Ulfah Rizky; Falah, Syaikhul; Tandililing, Elia Madatu; Puspitasari, Esti Diah (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Cenderawasih, 2023)
This research aims to determine the influence of perceived usefulness, perceived convenience, perceived security and confidentiality on taxpayer interest in using e-filing at KPP Pratama Jayapura City. The dependent variable used in this research is taxpayer interest in using e-filing, while the independent variables are perceived usefulness, perceived convenience, perceived security and confidentiality. The respondents are individual taxpayers who have used e-filing and have not used e-filing at KPP Pratama Jayapura City. This research uses multiple linear regression analysis with a sample of 100 respondents. The results show that perceived usefulness influences taxpayers' interest in using e-filing, perceived ease influences taxpayers' interest in using e-filing, perceptions of security and confidentiality influence taxpayers' interest in using e-filing, as well as perceived usefulness and ease of use. , perceptions of security and confidentiality jointly influence taxpayers' interest in using e-filing. Keywords ; Confidentally, Convenience, E-filling, Perceived Usefulness, Security, and Taxpayer